İmamlarda dünyevileşme eğilimi - Demir, Fatih (My University, 2019)
Kapitalizmin yaygınlık kazanması, rasyonel aklın, pozitivist düşüncenin ve bilimsel gelişmelerin artması, şehirleşmenin hızlanması ile yaşanan toplumsal değişimler, dünyevileşme veya diğer bir isimle sekülerleşme süreçlerini de beraberinde getirmiştir.Bu çalışmada, yirmi din görevlisiyle gerçekleştirilen mülakatlar ile imamların dünyevileşme eğiliminin izleri sürülmeye çalışılmıştır. Üç bölümden oluşan çalışmanın ilk bölümünde, sekülerleşmeye zaman içerisinde yüklenen anlamlar, sekülerleşme teorileri, sekülerleşme çeşitleri, sekülerleşme ve din ilişkisi incelenmiştir. İmamların sosyokültürel yapısının ele alındığı ikinci bölümde, imamların dini kaynaklardaki yeri, imamların geçmişten günümüze kadarki görev ve sorumlulukları ile imamların toplumdaki sosyoekonomik ve kültürel statüsü yer almıştır. Üçüncü bölümde, gerçekleştirilen mülakatlar neticesinde ulaşılan bulgular, detaylı bir şekilde irdelenerek değerlendirilmiştir. Sonuç kısmında, araştırma neticesinde elde edilen bulgulara genel bir perspektiften bakılmış, aynı zamanda gelecekteki çalışmalara katkı sağlayacağı düşünülen deneyimler ve öneriler paylaşılmıştır.

Changes in the society that are seen because of the spread of capitalism, becoming dominant of the rational mind and positivist thinking, increasing in scientific developments, and the acceleration of urbanization have been lead up to secularization processes.In this study, it has been tried to determine the secularization tendencies of imams through the interviews with twenty religious officials. In the first main part of study which consist of three main part, that are examined the meanings of secularization which have been attributed over time, theories of secularization, varieties of secularization, and relationship between religion and secularization. In the second main part, where the socio-cultural structure of the imams are examined in detail, the place of imams in religious sources, the duties and responsibilities of imams from past to present and the socio-cultural and economic status of imams in the society are also included. In the third main part which is the last main part, findings which are obtained thanks to interviews have been analyzed in detail. In the conclusion part, the consequences of the researches which are obtained by considering from a general perspective have been examined. Furthermore, the experiences and suggestions that are thought to be beneficial for the future studies have been shared.
Keywords: Din Adamları Secularization; Din Görevlileri; Dünyevileşme; Imams; Islam; İmamlar; İslamiyet; Religious Officials; Secularism; Sekülerizm; Sekülerleşme